The Study of Factors Influencing Tourists’ Revisit Intention To Cultural Tourism Destination In Surakarta City (Journal of Business and Management, 2022)
Abstract. Tourism industry is impactful for Indonesia's economy, it is supported by the country's resources, especially the diversity in nature, culture, and historical resources. The data shows that cultural tourism is dominating the industry. The study refers to a specific tourist behavior in cultural tourism, that they tend to be driven by education which makes them likely to not revisit. This can result in absence of tourist loyalty and continuous market success of cultural destinations. Therefore, this study aims to understand factors that influence tourists' revisit intention. The study’s scope is in Surakarta, it is a quantitative study that analyzes the data using the kruskal-wallis and PLS-SEM. A total of 215 respondents were collected with criterias living outside Surakarta City, Indonesian citizens, and have visited at least one of model destinations: Pura Mangkunegaran and Keraton Surakarta Hadiningrat. These study results support the ideas that travel motivation, cultural contact, perceived value, and tourists’ satisfaction has a positive influence on tourists' revisit intention. This study also highlights that cultural aspects are indeed crucial, thus the destination must emphasize the cultural aspect. Other several possible recommendations are to manage tourists' satisfaction and perceived value, manage cultural activities, and utilize social media as advertising tools.Keywords: Tourist, Tourism, Cultural Tourism, Surakarta City, and Revisit Intention